2011
DOI: 10.1186/1756-9966-30-85
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of NF-κB and Notch1 signaling contribute to tumor-induced lymphangiogenesis of esophageal squamous cell carcinoma

Abstract: BackgroundLymph node involvement and tumor-induced lymphangiogenesis appear as the earliest features of esophageal squamous cell carcinoma (ESCC), although the molecular regulatory mechanisms involved have remained unclear. Our aim was to investigate the contribution of NF-κB and Notch1 signaling to lymph node involvement and tumor-induced lymphangiogenesis in ESCC.Material and methodsNF-κB and Notch1 expression in 60 tissue samples of ESCC were assessed by immunohistochemical staining. The correlations of NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Both immunohistochemistry and real-time PCR experiments demonstrated a strong association of ALDH1 with the reversed NOTCH1 expression in breast cancer. Although several studies showed that NOTCH family member levels were elevated in various breast tumor samples and cell lines and upregulation of specific NOTCH proteins would lead to increased tumor cell proliferation and invasion [33-35], our findings demonstrated that moderate or high expression of NOTCH1 was parallel to the absence or little expression of ALDH1 expression and this inconsistency seemed NOTCH signaling pathway may played a negative role on ALDH1-positive breast cancer cells, which was similarly with the finding that NOTCH signaling might serve as a tumor suppressor in some solid tumors [21,22]. Thus, clinical benefits by regulation of NOTCH potentially in targeting ALDH1-positive breast cancer cells may be a complex question worth researching.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Both immunohistochemistry and real-time PCR experiments demonstrated a strong association of ALDH1 with the reversed NOTCH1 expression in breast cancer. Although several studies showed that NOTCH family member levels were elevated in various breast tumor samples and cell lines and upregulation of specific NOTCH proteins would lead to increased tumor cell proliferation and invasion [33-35], our findings demonstrated that moderate or high expression of NOTCH1 was parallel to the absence or little expression of ALDH1 expression and this inconsistency seemed NOTCH signaling pathway may played a negative role on ALDH1-positive breast cancer cells, which was similarly with the finding that NOTCH signaling might serve as a tumor suppressor in some solid tumors [21,22]. Thus, clinical benefits by regulation of NOTCH potentially in targeting ALDH1-positive breast cancer cells may be a complex question worth researching.…”
Section: Discussionsupporting
confidence: 82%
“…Previously, up regulation of NOTCH ligands led to elevation of the mammosphere number, and conversely, down regulation abrogated mammosphere formation, providing evidence that the NOTCH signal pathway contributes to mammary gland development [18]. On the other hand, although overexpression of NOTCH ligands in a transgenic mouse model triggered breast cancer, supporting the theory that NOTCH contributes to cancer development [19,20], the finding that NOTCH signaling is diminished in some solid tumors would seem to suggest that NOTCH might serve as a tumor suppressor [21,22]. However, no evidence of an association of the NOTCH signaling pathway with proliferation or suppression of the ALDH1-expressing cellular subcomponent displaying early tumor relapse characteristics has been obtained to date.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Notch-1 was widely studied and reported to aberrantly express in malignant tumors [15-19]. It was considered as a highly controversial gene because of its complex biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…One particular function of NF-κB is to promote cell survival through the induction of target genes, whose products inhibit components of the apoptotic machinery in normal and cancerous cells (33). It has been demonstrated that NF-κB plays a key role in progression, apoptosis and lymph node metastasis in ESCC (3436). As a downstream component of the PI3K/Akt pathway (37), NF-κB primarily resides in the cytosol in an inactive form; a heterodimer composed of p50 and p65 through an interaction with the inhibitory protein IκB (38).…”
Section: Discussionmentioning
confidence: 99%